Agrarnaia nauka: vyzovy i perspektivy - Antoeva A. S. (Agrarian science: challenges and prospects, 2018)
The collection includes materials of the regional conference "Agrarian Science – сhallenges and prospects", held on November 30, 2018 in Yakutsk. The collection summarizes the results of scientific research and methodological developments in the field of agricultural education, agricultural production, engineering and technical support of the agro-industrial complex and the forest complex. Materials are published in the author's edition. The collection is intended for heads and specialists of agricultural production, teachers, graduate students and students of higher educational institutions, employees of scientific institutions.
Keywords: инновации; технологии; продуктивность; динамика; сельское хозяйство; экология; лесное хозяйство; лечение; экспертиза; agriculture; forestry; innovations; technologies; Productivity; treatment; dynamics; expertise; ecology